Effect of Liothyronine Treatment on Quality of Life in Female Hypothyroid Patients With Residual Symptoms on Levothyroxine Therapy: A Randomized Crossover Study - Bjerkreim, Betty Ann; Hammerstad, Sara Salehi; Gulseth, Hanne Løvdal; Berg, Tore Julsrud; Omdal, Lars Johan; Lee-Ødegård, Sindre; Eriksen, Erik Fink (Frontiers in Endocrinology, 2022)
Objective: The effects of levothyroxine (LT4)/liothyronine (LT3) combination therapy on quality of life (QoL) in hypothyroid patients former on LT4 monotherapy have been disappointing. We therefore wanted to test the effects of LT3 monotherapy on QoL in hypothyroid women with residual symptoms despite thyroid stimulating hormone (TSH) values within the reference range. Design: Female hypothyroid patients with residual symptoms on LT4 monotherapy or combination LT4/LT3 therapy received LT3 and LT4 monotherapy, respectively for 12 weeks in a non-blinded randomized crossover study. Methods: Fifty-nine patients aged 18-65 years were included. QoL was assessed using one disease-specific questionnaire (ThyPRO) and two generic questionnaires (Fatigue Questionnaire and SF-36) at baseline and at the end of the two treatment periods. Clinical indices of cardiovascular health (resting heart rate and blood pressure), as well as thyroid tests, were assessed at baseline and at the end of the two treatment periods. Results: After 12 weeks of LT3 treatment, 12 of the 13 domains of the ThyPRO questionnaire (physical, mental and social domains) showed significant improvements. The most pronounced improvements were less tiredness (mean -21  26; P<0.0001) and cognitive complaints (mean -20  20; P<0.0001). LT4 monotherapy exerted minor effects on two domains only (cognitive complaints and impaired daily life). All three dimensions’ scores in the Fatigue Questionnaire (physical, mental and total fatigue) improved after LT3 treatment compared to baseline (P<0.001), and in the SF-36 questionnaire 7 of 8 scales showed significantly better scores after LT3 treatment compared to baseline. There were no differences in blood pressure or resting heart rate between the two treatment groups. TSH in patients on LT3 was slightly higher (median 1.33 mU/L (interquartile range (IQR) 0.47-2.26)) than in patients on LT4 (median 0.61 mU/L (IQR 0.25-1.20; P<0.018). Conclusions: LT3 treatment improved QoL in women with residual hypothyroid symptoms on LT4 monotherapy or LT4/LT3 combination therapy. Short-term LT3 treatment did not induce biochemical or clinical hyperthyroidism, and no cardiovascular adverse effects were recorded. Further studies are needed to assess the long-term safety and efficacy of LT3 monotherapy. ClinicalTrials.gov identifier: NCT03627611